The role of ghrelin and ghrelin-receptor gene variants and promoter activity in type 2 diabetes. - Garcia, E; King, P; Sidhu, K; Ohgusu, H; Walley, A; Lecoeur, C; Gueorguiev, M; Khalaf, S; Davies, D; Grossman, AB; Kojima, M; Petersenn, S; et al. (2009)
BACKGROUND: Ghrelin and its receptor play an important role in glucose metabolism and energy homeostasis, and therefore they are functional candidates for genes carrying susceptibility alleles for type 2 diabetes. METHODS: We assessed common genetic variation of the ghrelin (GHRL; five single nucleotide polymorphisms (SNP)) and the ghrelin-receptor (GHSR) genes (four SNPs) in 610 Caucasian patients with type 2 diabetes and 820 controls. In addition, promoter reporter assays were conducted to model the regulatory regions of both genes. RESULTS: Neither GHRL nor GHSR gene SNPs were associated with type 2 diabetes. One of the ghrelin haplotypes showed a marginal protective role in type 2 diabetes. We observed profound differences in the regulation of the GHRL gene according to promoter sequence variants. There are three different GHRL promoter haplotypes represented in the studied cohort causing up to 45% difference in the level of gene expression, while the promoter region of GHSR gene is primarily represented by a single haplotype. CONCLUSION: The GHRL and GHSR gene variants are not associated with type 2 diabetes, although GHRL promoter variants have significantly different activities.